The FGM bivariate lifetime copula model: a bayesian approach - Suzuki. A. K.; Louzada-Neto Neto, Franscisco; Cancho, Vicente G.; Barriga, Gladys Dorotea Cacsire [UNESP] (My University, 2011)
In this paper, we propose a bivariate distribution for the bivariate survival times based on Farlie-Gumbel-Morgenstern copula to model the dependence on a bivariate survival data. The proposed model allows for the presence of censored data and covariates. For inferential purpose a Bayesian approach via Markov Chain Monte Carlo (MCMC) is considered. Further, some discussions on the model selection criteria are given. In order to examine outlying and influential observations, we present a Bayesian case deletion influence diagnostics based on the Kullback-Leibler divergence. The newly developed procedures are illustrated via a simulation study and a real dataset.
Keywords: Case deletion influence diagnostics; Copula modeling; Survival data; Bayesian approach